Resistome Analysis of Global Livestock and Soil Microbiomes - Lawther, Katie; Santos, Fernanda Godoy; Oyama, Linda Boniface; Rubino, Francesco; Morrison, Steven; Creevey, Chris J.; McGrath, John W.; Huws, Sharon Ann (Frontiers in Microbiology, 2022)
Antimicrobial resistance (AMR) is a serious threat to public health globally, it is estimated that AMR bacteria caused 1.47 million deaths in 2019 and this is set to rise to 10 million deaths annually. Agricultural environments act as antimicrobial resistance gene reservoirs, operating as a link between different ecosystems, enabling the mixing and dissemination of resistance genes. Due to the close interactions between humans and agricultural environments, these AMR gene reservoirs are a great risk to both human and animal health. In this study, we aim to identify the resistance gene reservoirs present in four agricultural microbiomes: poultry, ruminant, swine and soil. This large study brings together every available poultry, swine, ruminant and soil shotgun metagenomic sequence available on the NCBI sequence read archive for the first time. We use the ResFinder database to identify resistance genes in over 5,800 metagenomes. Antimicrobial resistance genes were diverse and widespread within the metagenomes, 235, 101, 167 and 182 different resistance genes were identified in the poultry, ruminant, swine and soil microbiomes respectively. The tetracycline resistance genes were the most widespread in the livestock microbiomes, including tet(W)_1, tet(Q)_1, tet(O)_1, and tet(44)_1. The tet(W) resistance gene was found in 99% of livestock microbiome metagenomes, while tet(Q) was identified in 93%, tet(O) in 82% and finally tet(44) in 69%. Metatranscriptomic analysis confirmed these genes were real and expressed in one or more of the livestock microbiomes, with tet(40) and tet(O) expressed in all three livestock microbiomes. In soil the most abundant gene was the oleandomycin resistance gene, ole(B). Fifty-five resistance genes were shared by the four microbiomes, with 11 resistance genes actively expressed in two or more microbiomes. By using all available metagenomes we were able to mine a large number of samples and describe agricultural resistomes in 32 countries. This study provides a global insight into the diverse and abundant antimicrobial resistance gene reservoirs present in both livestock and soil microbiomes.